2018
DOI: 10.2174/1570180815666180219164334
|View full text |Cite
|
Sign up to set email alerts
|

New 1,3-oxazolylphosphonium Salts as Potential Biocides: QSAR Study, Synthesis, Antibacterial Activity and Toxicity Evaluation

Abstract: Background: Due to the increase of multidrug-resistant microorganisms, the search for biologically active molecules does not stop. In the present study, we developed the effective QSAR model which allows a quick search of new potential Staphylococcus aureus inhibitors in the series of quaternary phosphonium salts. A number of the most promising 1,3-oxazol-4-yltriphenylphosphonium derivatives with predicted activities were synthesized and examined to confirm their antibacterial properties and the accuracy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…They are used for imaging and diagnosing tumors, and also as anticancer (Madar et al, 2007), antioxidant (Sheu, Nauduri, & Anders, 2006), antiviral, and antiparasitic agents (Spivak et al, 2014). PILs are also used extensively to fight bacterial and fungal infections (Trush et al, 2018). and additionally as biocides and antifouling agents (Joseph et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They are used for imaging and diagnosing tumors, and also as anticancer (Madar et al, 2007), antioxidant (Sheu, Nauduri, & Anders, 2006), antiviral, and antiparasitic agents (Spivak et al, 2014). PILs are also used extensively to fight bacterial and fungal infections (Trush et al, 2018). and additionally as biocides and antifouling agents (Joseph et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Substances of interest were synthesized and screened for their antibacterial activity towards Staphylococcus aureus ATCC 25923 and Staphylococcus. According to performed antibacterial tests all compounds demonstrated the expected activity towards bacteria (Holovchenko et al, 2018).…”
Section: Other Theoretical Molecular Descriptorsmentioning
confidence: 87%
“…Authors demonstrated that RBN and Mv of HBD compounds showed positive effects on cytotoxicity of tested ILs, then the molar ratio of HBA to HBD and the number of HBD carbons exhibited the negative impact on activity of ILs. Models of minimal inhibitory concentration (Holovchenko et al, 2018) were developed based on data for 242 ILs from the OCHEM database (Sushko et al, 2011). According to the predictions obtained, the authors (Holovchenko et al, 2018) supposed that 1,3-oxazol-4-yl(triphenyl)phosphonium derivatives have antibacterial activities.…”
Section: Other Theoretical Molecular Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these groups is the lipophilic triphenyl-phosphonium (TPP) ion [30][31][32]. Indeed, the derivatives, bearing quaternary phosphonium salts were reported to show high antimicrobial activities [33][34][35] so that these cations were considered as a new generation of effective antiseptics. As pharmacological agents, TPP salts found to have also antiglycemic properties [36] and antiproliferative [36], antioxidant [37], antiviral activities [34].…”
mentioning
confidence: 99%